Molecular mechanisms underlying floral fragrance in Camellia japonica ‘High Fragrance’: a time-course assessment - Chen, Xuemei; Zhang, Xueping; Li, Yongquan; Tian, Xueqin; Tian, Xueyi; Zhao, Hongjie; Xuan, Zuying; Xue, Kena; Li, Yongjuan; Lin, Wei (Frontiers in Plant Science, 2024)
Camellia japonica 'High Fragrance' is a camellia hybrid known for its unique and intense floral scent. The current understanding of the dynamic changes in its fragrance and the underlying mechanisms are still limited. This study employed a combination of metabolomic and transcriptomic approaches to reveal the characteristics of the metabolites involved in the remarkable fragrance of this camellia and their biosynthetic mechanisms along three flower developmental stages (flower bud, initial bloom, and full bloom). Among the 349 detected volatile organic compounds (VOCs), the majority were terpenes (57, 16.33%) and esters (53, 15.19%). Of these, 136 VOCs exhibited differential accumulation over time. Transcriptomic data from floral organs at different flowering stages identified 56,303 genes, with 13,793 showing significant differential expression. KEGG enrichment analysis revealed 57, 91, and 33 candidate differential genes related to the biosynthesis of terpenes, phenylpropanoids, and fatty acid derivatives, respectively. This indicates that terpenes, esters, and their related synthetic genes might play a crucial role in the formation of 'High Fragrance' characteristics. During the entire flowering process, the majority of genes exhibited an elevated expression pattern, which correlated with the progressive accumulation of VOCs. Interestingly, the expression patterns of the differentially expressed genes in the mevalonate (MVA) and 2-C-methyl-D-erythritol 4-phosphate (MEP) pathways, associated with terpene synthesis, showed opposite trends. A transcriptional-metabolic regulatory network linking terpenoid compounds, related synthetic enzymes, and potential transcription factors could be outlined for 'High Fragrance' camellia, thus providing a theoretical basis for further exploring these events and breeding more fragrant camellias.